Vital activity limitation in patients with juvenile chronic arthritis - Tatyana Andreyevna Shelepina (Современная ревматология, 2012)
The results of examination using the CHAQ are employed to analyze the degree of vital activity limitation in patients with different types of juvenile chronic arthritis. Whether it is advisable to use the questionnaire in young preschoolers is discussed.